Conventional and comprehensive oral hygiene procedures using Chlorhexidine 0.2% in patients with mechanical ventilator - Fatoni, Arie Z.; Jaya, Wiwi; Muzzaman, Mussalam A. K. (International Journal of Research in Medical Sciences, 2019)
Background: Ventilator-Associated Pneumonia (VAP) in the intensive care unit patients is related to the oropharyngeal bacteria colonization. The purpose of this study was to compare the number of oropharyngeal bacterial colonies after conventional and comprehensive oral hygiene procedures in patients with mechanical ventilators. Methods: This study uses an experimental design on 32 subjects with mechanical ventilators. Conventional group/K group (n=16) used 0.2% chlorhexidine gluconate antiseptic conventionally using a sterile gauze while the comprehensive group/L group (n=16) used 0.2% chlorhexidine gluconate antiseptic comprehensively using a toothbrush every 12 hours. Bacterial Isolation is done using swab technique. The number of bacterial colonies and bacterial identification before and after oral hygiene procedure was examined. The data were statistically analyzed using the Wilcoxon test and the Mann Whitney test using SPSS 19.0 software. Results: There was a significant decrease in the number of oropharyngeal bacterial colonies before and after oral hygiene both in the conventional group (p=0.002) and comprehensive group (p=0.002). However, there was no significant difference between the number of bacterial colonies in the two groups before (p=0.269) and after the oral hygiene procedure (p=0.295). The most common bacterium in the conventional and comprehensive group are Enterobacter gergoviae and Escherichia coli, respectively. Klebsiella pneumonia have decreased the most after conventional oral hygiene while Pseudomonas aeruginosa has decreased the most after comprehensive oral hygiene. Conclusions: Conventional and comprehensive oral hygiene significantly reduces the number of oropharyngeal bacterial colonies. Both techniques can be used as oral hygiene techniques with relatively similar results.